A parceria público-privada da Arena Fonte Nova e a Copa de 2014 em Salvador: a ilusão do desenvolvimento - COSTA, Sheila Pires (2014)
This work analyzes the contribution of public-private partnership of the Arena Fonte Nova for the development of Salvador. The objective is to evaluate the use of public-private partnership Arena Fonte Nova instrument to induce the development of Salvador in the preparation of the 2014 World Cup in the period between 2009 and 2013. This is a single case study, it was selected for public- private partnership Arena Fonte Nova, considering the importance of reconstruction, essential for Salvador host matches of the World Cup 2014. Through the study it was realized that the preparation for the event attracted reduced amount of federal public and private investment, created few jobs and few social benefits brought works with small impact on the lives of the majority of the population of Salvador, in addition to generating the amount of lower than expected tax and tax breaks. There was also damage to other sports with the demolition of the old structure of the Fonte Nova stadium. About the PPP contract, realizes the guarantee of great advantages to the private partner without guarantee of the interests of the population, which can be verified by type and excessive concession period , the repayment of funds borrowed, tax incentives and value of public consideration.